1988
DOI: 10.1093/ije/17.3.608
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy and Health: Cardiovascular and Other Diseases Following Vasectomy in Sichuan Province, People's Republic of China

Abstract: The long-term sequelae of vasectomy were studied in a retrospective cohort study of 4596 vasectomized and 4340 nonvasectomized farmers from eight rural communes in Sichuan, People's Republic of China. The mean duration since the operation was 14.5 years with a range of 10 to 25 years. At the time of evaluation the vasectomized men were generally healthier than the non-vasectomized for a wide range of health indicators including clinical signs of cardiovascular disease, resting ECG changes, positive ECG changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Moreover, 2 were cross-sectional, [ 19 , 25 ] 4 were case–control, [ 17 , 18 , 21 , 26 ] and 6 were retrospective cohort studies. [ 20 , 22 24 , 27 , 28 ] The publication years of the included studies ranged from 1981 to 2005. Among them, seven were conducted in the United States, [ 19 , 20 , 23 26 , 28 ] 1 in China, [ 27 ] 2 in England, [ 21 , 22 ] and 2 in Korea.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, 2 were cross-sectional, [ 19 , 25 ] 4 were case–control, [ 17 , 18 , 21 , 26 ] and 6 were retrospective cohort studies. [ 20 , 22 24 , 27 , 28 ] The publication years of the included studies ranged from 1981 to 2005. Among them, seven were conducted in the United States, [ 19 , 20 , 23 26 , 28 ] 1 in China, [ 27 ] 2 in England, [ 21 , 22 ] and 2 in Korea.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 , 22 24 , 27 , 28 ] The publication years of the included studies ranged from 1981 to 2005. Among them, seven were conducted in the United States, [ 19 , 20 , 23 26 , 28 ] 1 in China, [ 27 ] 2 in England, [ 21 , 22 ] and 2 in Korea. [ 17 , 18 ] Furthermore, 6 studies were performed among the middle-aged and elderly populations, [ 17 24 , 26 28 ] but one study did not report this.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several long‐term studies of vasectomised patients have produced no evidence of increased cardiovascular disease 72‐76 . Some studies have even shown that cardiovascular disease may indeed be less common in the vasectomised population 72,74,76 . It is difficult to reconcile the results of these studies with the observations of arterial disease in vasectomised animals fed on atherogenic diets.…”
Section: How Safe Is Vasectomy?mentioning
confidence: 99%